Avaliação da política pública de acessibilidade urbana em Fortaleza/CE: o estudo de um trecho do Bairro Jardim Cearense - Soares, Morgana Costa (2022)
The general objective of this study is to investigate the accessibility of sidewalks for pedestrians and for people with disabilities or reduced mobility, in a stretch located in the Jardim Cearense neighborhood, Fortaleza/CE. Thus, the research unfolds in the following specific objectives, which are: a) to discuss the meaning of the category urbanity and its multiple unfoldings in the social sciences, based on the right to an accessible city; b) to know the singularities of the urban context of Fortaleza regarding the mobility and accessibility of sidewalks and c) to evaluate the public policy concerning the City Code in the investigated stretch. The methodological path, when trying to evaluate a public policy focused on urban mobility, relied on the qualitative approach, being this a strategy of academic investigation, used mainly in the social sciences. Moreover, as for the technical procedures, we resorted to bibliographic research, considering that according to Gil (2019), this constitutes the theoretical framework or preliminary study. Strictly speaking, we entered the documentary research, through the analysis of laws, decrees and news that concerned the object of investigation, including, it was necessary the field research, through the technique of structured questionnaire, with 9 questions, directed to 10 passersby, residents of that stretch and two questions to 10 inspectors of the Agency of Inspection of Fortaleza (AGEFIS). In face of the surveys, we detected that in the analysis of the sidewalks of the chosen route, incongruences were verified in the state of conservation, in the floor, in the dimensions, in the conditions of accessibility and in the obstructions found on the sidewalks, in consideration of the technical norms and laws. In short, the difference between what is proposed by legislation for the construction or reconstruction of sidewalks and what is observed in practice was verified, demonstrating the vulnerability of municipal public policy regarding the accessibility of the sidewalks in that spatial area.